2018
DOI: 10.1007/s10482-018-1035-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29

Abstract: Accumulated evidence suggests that root exudates have a major role in mediating plant-microbe interactions in the rhizosphere. Here, we characterized tobacco root exudates (TREs) by GC-MS and nicotine, scopoletin, and octadecane were identified as three main components of TREs. Qualitative and quantitative chemotaxis assays revealed that Pseudomonas aeruginosa NXHG29 with antagonistic activity displayed positive chemotactic responses towards TREs and their three main components (nicotine, scopoletin, octadecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Qualitative analyses of the freeze-dried tobacco and pepper root exudates were performed by GC-TOF-MS, and 248 peaks ( Supplementary Figure 2 ) were detected, including amino acids, organic acids, and others (data not shown). Here, some organic acids (cinnamic acid, fumaric acid, phthalic acid, benzoic acid, and lauric acid) and nicotine were selected as the targets for evaluation of their roles on B. velezensis GUMT319 ( Zhang et al, 2014 ; Feng et al, 2018 ; Ma et al, 2018 ). Cinnamic acid, fumaric acid, and benzoic acid were detected both in tobacco and pepper root exudates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative analyses of the freeze-dried tobacco and pepper root exudates were performed by GC-TOF-MS, and 248 peaks ( Supplementary Figure 2 ) were detected, including amino acids, organic acids, and others (data not shown). Here, some organic acids (cinnamic acid, fumaric acid, phthalic acid, benzoic acid, and lauric acid) and nicotine were selected as the targets for evaluation of their roles on B. velezensis GUMT319 ( Zhang et al, 2014 ; Feng et al, 2018 ; Ma et al, 2018 ). Cinnamic acid, fumaric acid, and benzoic acid were detected both in tobacco and pepper root exudates.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that organic acids were the most represented class of compounds in both plants. Hence, some organic acids (cinnamic acid, fumaric acid, phthalic acid, benzoic acid, and lauric acid) ( Zhang et al, 2014 ; Feng et al, 2018 ) and nicotine ( Ma et al, 2018 ) were selected as targets for the evaluation of their roles on B. velezensis GUMT319. Cinnamic acid, fumaric acid, and benzoic acid were detected both in tobacco and pepper root exudates, phthalic acid and nicotine in tobacco root exudates, and lauric acid only in pepper root exudates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QS is an intercellular communication system, in which particular signal molecules including AHLs mediate bacterial gene expression and bacterial cell concentration [90]. In fact, QS system controls the production of a variety of phenotypes, many of which have been linked to pathogenesis in a variety of economically significant bacterial pathogens, such as Pectobacterium carotovorum, Pseudomonas syringae, Dickeya solani, Ralstonia solanacearum, Erwinia amylovora, and Agrobacterium tumefaciens [91]. In agriculture, interference or interrupting QS is thus an intriguing technique for preventing pathogen infections [92].…”
Section: Microbe-microbe Interactionsmentioning
confidence: 99%
“…Quorum quenching (QQ), involving the enzymatic destruction of AHL signal molecules, is one of the most well-known QS-interrupting techniques [93]. For example, the QQ activity of Pseudomonas segetis strain P6 reduced soft rot symptoms on potato and carrot caused by D. solani, P. carotovorum, and Pectobacterium atrosepticum [91]. Moreover, plants are also able to disrupt the QS system by producing QS inhibitors, which either degrade QS signals or compete for signal receptors.…”
Section: Microbe-microbe Interactionsmentioning
confidence: 99%